2013
DOI: 10.1680/geot.12.p.067
|View full text |Cite
|
Sign up to set email alerts
|

Pipe uplift in saturated sand: rate and density effects

Abstract: A key parameter for assessing the unburial behaviour of offshore pipelines, such as during upheaval buckling, is the soil uplift resistance. Despite much research on uplift response, two variables remain relatively unexplored: the effect of low relative density backfill and partially drained soil response. To address this shortcoming, an investigation into the plane-strain uplift resistance of pipe segments in saturated sand was carried out. The model tests, targeting drained and partially drained soil behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…The transition to a flow-around failure as reported in the companion paper (see Fig. 5(b) of the companion paper (Williams et al, 2013)) could well be related to this vertical stress limit. (Interestingly if one checks the above vertical stress limit based on the horizontal stress at the centre line of the pipe, rather than at the crown -that is, replacing the factor (H À D/2) in the above by H -and considering the friction angle of the soil tested, one obtains a transition from vertical slip model to the vertical stress limit being the governing condition as H/D rises above 2 .…”
Section: Vertical Stress Limitsupporting
confidence: 60%
See 3 more Smart Citations
“…The transition to a flow-around failure as reported in the companion paper (see Fig. 5(b) of the companion paper (Williams et al, 2013)) could well be related to this vertical stress limit. (Interestingly if one checks the above vertical stress limit based on the horizontal stress at the centre line of the pipe, rather than at the crown -that is, replacing the factor (H À D/2) in the above by H -and considering the friction angle of the soil tested, one obtains a transition from vertical slip model to the vertical stress limit being the governing condition as H/D rises above 2 .…”
Section: Vertical Stress Limitsupporting
confidence: 60%
“…The paper by Byrne et al (2013) together with the companion paper by Williams et al (2013) present perhaps the most comprehensive and systematic set of upheaval resistance tests in saturated clean sand. The results also appear very consistent with the theories and explanations provided, which further attests to the quality of the experimental work, and the power of the relatively simple model for development and dissipation of excess pore pressure, and the vertical slip model for uplift resistance.…”
Section: Contribution By R Peekmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when the rate of testing exceeds this limiting value, partially drained conditions will apply and this will affect the peak mobilisation displacement. Williams et al (2013) showed that the mobilisation displacement will increase for speeds in the range 0?002-5 mm/s. A recent full-scale experimental study was undertaken at the University of Cambridge in sandy backfill (Thusyanthan et al, 2010;Wang et al, 2012) to investigate the uplift stiffness response of pipelines buried in both saturated and dry sand.…”
Section: Introductionmentioning
confidence: 99%